CORRELATION RELATIONSHIPS BETWEEN PERCEPTION OF INTERPERSONAL INTELLIGENCE WITH AFFECTIVE STUDENTS IN CURRICULUM DEVELOPMENT IN ELEMENTARY TEACHER EDUCATION STUDY PROGRAM OF PAKUAN UNIVERSITY - Nurlinda Safitri; Sriyamto . (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
This research is a correlational design and quantitative research model. The purpose of this study was to describe information about the correlation relationship between Interpersonal Intelligence Perception and Affective Students in Curriculum Development Courses in fifth Semester students of the Elementary Teacher Education Study Program (PGSD) of Pakuan University. Based on the results of research on questionnaire data recapitulation and documentation, it can be concluded that there is a positive and significant relationship between the perceptions of interpersonal intelligence with the affective variables of the fifth semester students of class A and B PGSD Study Program, which means the more interpersonal intelligence students have, the more also high affective, and vice versa the lower the interpersonal intelligence, the lower the affective. The relationship can be seen from the price coefficient of 0.921, which means that the relationship between variables is very strong. The coefficient of regression equation Ŷ = 23.67 + 0.68X, which means that each increase in one unit of interpersonal intelligence will increase the effectiveness of 0.68 units. The contribution of perceptions of interpersonal intelligence in increasing affective is 0.53 or 53% and the remaining 47% can be influenced by several other factors.